INOVASI PEMBUATAN SIDE DISH HUMMUS DENGAN PENAMBAHAN TEMPE SEBAGAI PRODUK PANGAN LOKAL - Surya Adytya Kurniawan; Ita Fatkhur Romadhoni; Lilis Sulandari; Qorry' Aina (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to determine the sensory characteristics of tempeh hummus with various levels of tempeh addition and to identify the formulation that produces the highest level of preference among panelists. The study used an experimental quantitative design with three treatments of tempeh addition: 30 grams, 40 grams, and 50 grams. Sensory evaluation included attributes of color, aroma, texture, taste, and overall preference by 35 panelists, consisting of 3 trained panelists and 32 semi-trained panelists. Data were analyzed using One-Way Analysis of Variance (ANOVA) at a 5% significance level, followed by further tests if significant differences were found. The results showed that variations in tempeh addition significantly affected the texture of the product (Sig. 0.006 < 0.05), but did not significantly affect color (Sig. 0.52), aroma (Sig. 0.806), taste (Sig. 0.261), or overall preference (Sig. 0.691). The best formulation was the addition of 40 grams of tempeh, which achieved the highest average scores in color (3.57), aroma (3.77), texture (3.97), taste (3.53), and overall preference (3.47). In conclusion, adding 40 grams of tempeh is the optimal amount, yielding the best sensory quality, maintaining the creamy texture characteristic of hummus, and effectively integrating the local identity of tempeh.